Mucha — Habermann acute varioliform parapsoriasis with the formation of hypertrophic scars in a teenager - E. V. Pavlova; I. V. Ulitina; E. N. Efanova (Лечащий Врач, 2022)
The article describes a case of Mucha – Habermann varioliform (smallpox-like) parapsoriasis in a teenager. Parapsoriasis is a heterogeneous group of chronic inflammatory dermatoses that are characterized by the presence of spots and/or papules and plaques covered with small scales. The relevance of parapsoriasis is due to the ambiguity of the etiopathogenetic mechanisms of the disease, the lack of a generally accepted classification. Interest in the disease is partly due to the possibility of transformation of parapsoriasis to T-cell lymphoma (fungal mycosis). Description of the clinical case. Patient A., 14 years old, went to the skin and Venereological dispensary in Surgut with complaints of multiple rashes on the skin of the trunk and limbs, accompanied by minor soreness, burning and moderate itching. Ill for about 10 days, the beginning of the disease was associated with hypothermia. The appearance of the rash was preceded by a sharp rise in body temperature to 38 °C, chills, weakness, malaise. Objectively: the pathological skin process was widespread. Rashes were localized in the torso area on the skin of the chest, back, abdomen, upper and lower limbs. It is represented by multiple miliary and lenticular papules of pink-red color, pustules. In the Central part of most elements, zones of necrosis or ulcerative defects from 0,2 to 2 cm in diameter, hemorrhagic crusts were visualized. The diagnosis of acute varioliform parapsoriasis was made on the basis of clinical and anamnestic data and the results of additional research methods. The treatment used antibacterial drugs, detoxification methods, physiotherapy (light therapy). The outcome of treatment is improvement. When actively called after 6 months, hypertrophic and smallpox-like scars of the skin of the trunk and extremities were found during examination. This clinical example is of interest to dermatovenerologists and pediatricians. It illustrates the relative goodness of the course of dermatosis, despite the brightness and acuteness of clinical manifestations. Timely treatment has significantly improved both the child's condition and quality of life. Due to the rare occurrence of acute lichenoid parapsoriasis, doctors may experience difficulties in making a diagnosis. The case is presented in order to attract the attention of the medical community to the problem of parapsoriasis.